Ni-doped CdS porous cubes prepared from prussian blue nanoarchitectonics with enhanced photocatalytic hydrogen evolution performance. (19th January 2022) - Cao, Xianglei; Zhang, Liugen; Guo, Changyan; Chen, Tingxiang; Feng, Chao; Liu, Zechang; Qi, Ying; Wang, Wei; Wang, Jide
Abstract: In this paper, Nix Cdy S composite photocatalysts were synthesized by using Ni-doped Cd–Co PBA as the precursor, which retains the advantages of PBA such as porous structure, large specific surface and highly dispersed metal active sites. The photocatalytic hydrogen production performance over Nix Cdy S is three times higher than that of pure CdS with H2 yield of 8.45 mmol g −1  h −1 . The catalyst was analyzed by the UV/Vis absorption spectra, photoluminescence spectra, time-resolved photoluminescence spectra, transient photocurrent responses, electrochemical impedance spectra, Mott-Schottky test, etc. A series of characterization results prove that the electron-hole recombination rate, electrochemical resistance and band gap of nickel-doped CdS composites are obviously smaller than CdS, which are important factors to improve the photocatalytic hydrogen production performance. This work may provide some reference value for the fabrication of other functional materials using PBA as precursors. Graphical abstract: Image 1 Highlights: A synthesis strategy of excellent photocatalyst was developed by using PBA as precursor. Hydrogen generation increase up to 5 times because interaction between NiS and CdS. PBA based photocatalyst had large specific surface area. NiS and CdS are uniformly compounded by a simple method.